Impact of diagnosis and surgical treatment of early stage borderline ovarian tumours on distress, anxiety, and psychosexual health - Stefan Cosyns; Noëlie Dony; Nikolaos Polyzos; Ronald Buyl; Herman Tournaye; Christiaan Schotte (Taylor & Francis Group, 2024)
Women diagnosed with gynecological cancer are likely to face additional consequences beyond those common to all cancer patients leading to significant physical and psychological morbidity. Longitudinal studies addressing the prevalence of psychological distress, anxiety, or psychosexual health during follow-up in patients diagnosed with borderline ovarian tumors are lacking. This study explores this prevalence compared with controls who underwent comparable surgical treatment for benign ovarian tumors. A prospective 1:1 nonmatched case-control study was set up, registered on ClinicalTrials.gov under number NCT 04253327. Thirty early stage borderline ovarian tumor patients participated, and 30 controls were included. The study materials consisted of different questionnaires. A general one on patient's sociodemographic and medical information. A questionnaire about anxiety and distress made up of three validated questionnaires: Hospital Anxiety and Depression Scale, Perceived Stress Scale and Body Image Scale. As last one the psychosexual health questionnaire consisted of the Female Sexual Function Index, the Female Sexual Distress Scale and two European Organisation for Research and Treatment of Cancer questionnaires. Both groups were comparable and did not differ significantly in terms of demographic characteristics. Patients with early stage borderline ovarian tumors experience a significant higher burden of mental health issues due to disease and treatment and/or are more worried about their future health. Surprisingly, both early stage borderline ovarian tumor patients and controls showed high levels of anxiety and moderate stress. Many patients in both groups experience sexual dysfunction and distress. These findings support active screening for anxiety, depression and psychosexual perturbance during postoperative follow-up to accommodate this.